TINGKAT PARTISIPASI ANGGOTA KOPERASI UNIT DESA TANI BAHAGIA DI DESA KULIM JAYA KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Ardianto, Budi; Yulida, Roza; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Koperasi Unit Desa (KUD) is the closest and very importantinstitution, because this institution is very useful in the life of the rural economy. One of the co-operative which has the purpose of the welfare of its members, located in Kulim Jaya Village, namely KUD Tani Bahagia. The purpose of the cooperative is to meet the needs of its members.The purpose of this study are: 1). to determine the participation of members of Koperasi Tani Bahagia 2). to know the problems faced by members of Koperasi Tani Bahagia. The method used in this study was a survey method. Data collected include primary and secondary data.Results of the research have shown: 1). The overall participation level of members of the cooperative was categorized as high participation with the score of 3.55. Consisting of: A). The overall participation of members in decision-making activities was categorized in medium level with a score of 3.26. B). Participation of members in the implementation of the overall cooperative activities were classified in the high category with a score of 3.67. C). Participation of members in overall service utilization were classified in the high category with a score of 4.12. D). Participation of members in the overall evaluation classified in the high category with a score of 3.55. While on goal 2). Constraints faced by members were the lack of liveliness, presence, and lack of contributions to the meeting members of the cooperative and the calculation of net income. Keywords: Level of participation, cooperation and KUD Tani Bahagia